THE INFLUENCE OF COGNITIVE BEHAVIORAL THERAPY (CBT) BASED ON ISLAMIC VALUES ON GAMING ADDICTION ONLINE GAMES FOR SCHOOL-AGE CHILDREN - Mubin , M. Fatkhul; Syarif, Iqwan; Rejeki, Sri (Universitas Islam Negeri Alauddin Makassar, 2023)
Online game addiction is often characterized by the inability to control the desire to play so that it is difficult or unable to stop the behavior regardless of all the efforts made to stop it. This research aims to determine the effect of Cognitive Behavioral Therapy (CBT) based on Islamic values on addiction to playing online games in school-aged children. Design This research is a quasi-experiment with a two-group pretest and post-test design with the control group. The population in this study were grade 6 students from two elementary schools in Makassar City, South Sulawesi with a sample size of 64 respondents and taken by purposive sampling divided into control and intervention groups. The research instrument is a knowledge questionnaire. Data analysis using SPSS software. The research results explain that Asymp.Sig. (2-tailed) is 0.000, which shows that there is a difference in the level of knowledge in the intervention and control groups after being given CBT intervention with Islamic values because CBT with Islamic values was given to the intervention group. Meanwhile, before the intervention was given, there was no significant difference in the control and treatment groups with a value of 0.829 > 0.05. This means that there was no difference between the control and intervention groups before being given CBT with Islamic Values. Islamic Values CBT intervention can help in efforts to reduce the level of online gaming addiction in adolescents and can be used as an alternative nursing intervention in preventive efforts. Keywords: Online Games, Addiction, Cognitive Behavioral Therapy